Real Time Li-ion Battery Bank Parameters Estimation for Electric Vehicle Traction System - Butt, Hafiz Muhammad Usman (2019)
A Master of Science thesis in Electrical Engineering by Hafiz Muhammad Usman Butt entitled, “Real Time Li-ion Battery Bank Parameters Estimation for Electric Vehicle Traction System”, submitted in May 2019. Thesis advisor is Dr. Shayok Mukhopadhyay and thesis co-advisor is Dr. Habibur Rehman. Soft and hard copy available.